PENGEMBANGAN OBJEK WISATA PANTAI BATU BENGKUNG KABUPATEN MALANG DALAM PERSPEKTIF COLLABORATIVE GOVERNANCE - Tariza Noviranti Muhaling; Hasan Ismail (Universitas Mbojo Bima, 2023)
The purpose of this study is to analyze collaborative governance in the development of Batu Bengkung beach tourism objects in Malang Regency. Malang Regency has a wide variety of potential tourist objects, one of the leading tourist objects is beach tourism. Beach tourism objects are generally owned by the local Tourism Office, but in the South Malang Regency area, almost 90% of the beach tourism objects are managed by Perum Perhutani. The development of tourist objects continues to be carried out in order to increase the economic growth rate of Malang City, however there are differences in land ownership which makes the process of developing this beach tourism object a little more complicated. The theory used in this research is collaborative governance and development of tourist objects. This study uses a qualitative method with the type of approach used is a descriptive approach. The data collection method used is in the form of interviews, documentation, and literature studies on previous research.